2011
DOI: 10.3324/haematol.2011.043885
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of germline 46/1 haplotype of Janus kinase 2 in cytogenetically normal acute myeloid leukemia

Abstract: The online version of this article has a Supplementary Appendix. BackgroundPrognostic risk stratification according to acquired or inherited genetic alterations has received increasing attention in acute myeloid leukemia in recent years. A germline Janus kinase 2 haplotype designated as the 46/1 haplotype has been reported to be associated with an inherited predisposition to myeloproliferative neoplasms, and also to acute myeloid leukemia with normal karyotype. The aim of this study was to assess the prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
(39 reference statements)
1
14
0
1
Order By: Relevance
“…The lack of an association between leukemia‐free survival and the JAK2 46/1 haplotype further supports the notion that the adverse survival effect of nullizygosity for the JAK2 46/1 haplotype might be mediated by a predisposition to nongenetic causes of death. However, contrary to such suggestion, previous studies in patients with normal karyotype acute myeloid leukemia have instead implicated homozygous/heterozygous JAK2 46/1 haplotype as being associated with inferior survival, possibly related to increased risk of death from infection . In an elegant editorial that accompanied the latter study, Hermouet and Vilaine entertained the possibility that the JAK2 46/1 haplotype might be a marker of myelomonocytic dysfunction and might also provide fertile ground for the acquisition of additional mutations.…”
Section: Discussionmentioning
confidence: 94%
“…The lack of an association between leukemia‐free survival and the JAK2 46/1 haplotype further supports the notion that the adverse survival effect of nullizygosity for the JAK2 46/1 haplotype might be mediated by a predisposition to nongenetic causes of death. However, contrary to such suggestion, previous studies in patients with normal karyotype acute myeloid leukemia have instead implicated homozygous/heterozygous JAK2 46/1 haplotype as being associated with inferior survival, possibly related to increased risk of death from infection . In an elegant editorial that accompanied the latter study, Hermouet and Vilaine entertained the possibility that the JAK2 46/1 haplotype might be a marker of myelomonocytic dysfunction and might also provide fertile ground for the acquisition of additional mutations.…”
Section: Discussionmentioning
confidence: 94%
“…9 In the present issue of Haematologica, the same group found that the JAK2 46/1 haplotype is associated with an increased frequency of acute myelomonocytic leukemia and a tendency to reduced survival because of death from infection in patients with NK-AML. 10 The latter findings need confirmation by other studies, for it is of great interest to establish whether the JAK2 46/1 haplotype is in fact a marker of myelomonocytic dysfunction and subsequently an unfavorable risk factor in NK-AML, as Nahajevszky et al suggest, and/or in other disease categories. 10 In fact, although the majority of studies have failed to detect any association of the 46/1 haplotype with hematologic and clinical parameters (Table 1), Tefferi et al found that the 46/1 haplotype status influenced survival in primary myelofibrosis, and evolution toward myelofibrosis in polycythemia vera.…”
mentioning
confidence: 82%
“…10 The latter findings need confirmation by other studies, for it is of great interest to establish whether the JAK2 46/1 haplotype is in fact a marker of myelomonocytic dysfunction and subsequently an unfavorable risk factor in NK-AML, as Nahajevszky et al suggest, and/or in other disease categories. 10 In fact, although the majority of studies have failed to detect any association of the 46/1 haplotype with hematologic and clinical parameters (Table 1), Tefferi et al found that the 46/1 haplotype status influenced survival in primary myelofibrosis, and evolution toward myelofibrosis in polycythemia vera. 5 Moreover, it has been reported that the frequency of the JAK2 46/1 haplotype is increased in the context of severe inflammation, for instance Crohn's disease.…”
mentioning
confidence: 82%
“…Kedvező genetikai markerek (FLT3-ITD negatív, NPM/IDH mutáns betegek) esetén jobb, bizonyos mutációk (TET2, MLL-PTD, ASXLI, PHF-6) mellett rövidebb túlélés várható. Nahajevszky és mtsai [1] szerint a JAK2 (Janus kinase 2) 46/1 haplotípus szintén kedvezőtlen prognó-zist jelez normális citogenetikájú AML-es betegekben. A mutációs profil alapján a normális karyotypusú betegek kedvező, intermedier és kedvezőtlen prognózisú csoportba sorolhatók.…”
Section: öSszefoglaló Közleményunclassified